Opini Publik Mengenai Maraknya Publik Figure yang Melanggar Norma di Media Sosial - Anugrah, Tirta; Alif Ghani, Muhammad Fikri; Salsabila Purba, Maulida; Surbakti, Meliastaras; Effendi, Erwan (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
This research aims to describe public opinion regarding the rise of public figures who violate norms on social media. This research is a qualitative descriptive study. The research results show that a public figure is an influential person whose every behavior, attitude and activity becomes a public spectacle. So, a public figure needs to be careful in being positive in real life or on social media. There are several public figures who frequently violate norms in Indonesia, including artists, influencers and high-ranking officials. Examples of violations of norms are artists who say that they are transgender, artists who have pornography cases, artists who have bad attitudes, namely fighting through innuendo and harsh words on social media. Artists who commit sexual harassment and infidelity. Another example is an influencer who endorses a beauty product, which after investigation turns out to contain ingredients that are harmful to the skin. An example of this is high-ranking officials, namely where there are high-ranking officials who always display their luxury and wealth on social media, which turns out to be obtained from them committing corruption and bribery in their agencies. Public opinion regarding the violations of norms that occurred, namely the public's opinion to reject them by criticizing them on social media in the form of cyberbullying and cancel culture.